The use of courseware in teaching recorder year 5 / Nik Mansor Nik Mahmood @ Nik Mat - Nik Mahmood @ Nik Mat, Nik Mansor (2015)
World Of Music is a minor subjects taught in school. Various methods can be used to make the subject become more attractiveby students. The ICT-based learning can be helpful for students to have better understanding and thus able to achieve the objectives in teaching. This study was conducted to help students year 5 Fathonah in SK Kuala Balah Jeli, Kelantan to increase their understanding and memory in playing the recorder. The method used is by usingtheteaching and learning "courseware" in theclassroom.The Respondent consisted of 17 boys and 8 girls. The instruments used were observations and questionnaires .In the early stages of the study, researchers used the instruments in making the observations of the respondent during the teaching process. After completion of the first teaching session, researcher will complete a questionnaire in teaching results. The first lesson does not use the courseware. In the second stage, I will use the teaching courseware. Based on the analysis of observation and questionnaire, the use of courseware will help respondents to understand and comprehend recorders correctly. By using these methods, teaching and learning process become more enjoyable and attractive to the students.